Germination and initial growth of guava plants irrigated with saline water Germinação de sementes e crescimento inicial da goiabeira irrigada com água salina - Lourival F. Cavalcante; Ítalo H. L. Cavalcante; Kátia S. N. Pereira; Francisco A. de Oliveira; Saulo C. Gondim; Fernanda A. R. de Araújo (Revista Brasileira de Engenharia Agrícola e Ambiental)
The present study was carried in order to evaluate the effect of saline water irrigation with electrical conductivity (ECw) of 0.5; 1.5; 3.0; 4.5 and 6.0 dS m-1, on germination and some growth variables during the seedling formation process of four guava cultivars (Psidium guajava L.): Pentecoste, Paluma, Surubim and IPA B-38. Water salinity inhibited the germination process, plant height, stem diameter, leaf area and dry matter production of roots, stems and leaves, independently of cultivar. After germination, the seedlings did not survive due to saline water effects of ECw 4.5 and 6.0 dS m-1. After 180 days of sowing, the seedlings irrigated with ECw more than 1.5 dS m-1 did not present agronomic quality for planting. Dry matter production sequence of different parts of plants was as follows: leaves > roots > stems, without significant differences among cultivars especially when irrigated with saline water of ECw > 3.0 dS m-1. Avaliou-se o efeito da salinidade da água de irrigação, através dos níveis de condutividade elétrica (CEa) de 0,5; 1,5; 3,0; 4,5 e 6,0 dS m-1, sobre a germinação de sementes e algumas variáveis de crescimento, durante a formação de mudas de quatro cultivares de goiabeira (Psidium guajava L.) Pentecoste, Paluma, Surubim e IPA B-38. A salinidade da água inibiu a germinação, o crescimento em altura, diâmetro do caule, área foliar e fitomassa das raízes, caules e folhas das plantas, independente da cultivar. Após a germinação, as plântulas não sobreviveram aos efeitos salinos das águas de condutividade elétrica CEa 4,5 e 6,0 dS m-1. Ao final do ensaio, 180 dias após a semeadura, não se obtiveram mudas com qualidade agronômica nos tratamentos irrigados com água de salinidade superior a 1,5 dS m-1. A ordem de produção de matéria seca pelos distintos órgãos das plantas, foi: folhas > raízes > caules, mas sem diferir entre cultivares, principalmente quando irrigadas com água de maior salinidade > 3,0 dS m-1.